EC-tagging allows cell type-specific RNA analysis. Issue 15 (21st June 2017) - Hida, Naoki; Aboukilila, Mohamed Y.; Burow, Dana A.; Paul, Rakesh; Greenberg, Marc M.; Fazio, Michael; Beasley, Samantha; Spitale, Robert C.; Cleary, Michael D.
Abstract: Purification of cell type-specific RNAs remains a significant challenge. One solution involves biosynthetic tagging of target RNAs. RNA tagging via incorporation of 4-thiouracil (TU) in cells expressing transgenic uracil phosphoribosyltransferase (UPRT), a method known as TU-tagging, has been used in multiple systems but can have limited specificity due to endogenous pathways of TU incorporation. Here, we describe an alternative method that requires the activity of two enzymes: cytosine deaminase (CD) and UPRT. We found that the sequential activity of these enzymes converts 5-ethynylcytosine (EC) to 5-ethynyluridine monophosphate that is subsequently incorporated into nascent RNAs. The ethynyl group allows efficient detection and purification of tagged RNAs. We show that 'EC-tagging' occurs in tissue culture cells and Drosophila engineered to express CD and UPRT. Additional control can be achieved through a split-CD approach in which functional CD is reconstituted from independently expressed fragments. We demonstrate the sensitivity and specificity of EC-tagging by obtaining cell type-specific gene expression data from intact Drosophila larvae, including transcriptome measurements from a small population of central brain neurons. EC-tagging provides several advantages over existing techniques and should be broadly useful for investigating the role of differential RNA expression in cell identity, physiology and pathology.